2017
DOI: 10.1177/0394632017745762
|View full text |Cite
|
Sign up to set email alerts
|

Serratiopeptidase reduces the invasion of osteoblasts by Staphylococcus aureus

Abstract: Finding new strategies to counteract periprosthetic infection and implant failure is a main target in orthopedics. Staphylococcus aureus, the leading etiologic agent of orthopedic implant infections, is able to enter and kill osteoblasts, to stimulate pro-inflammatory chemokine secretion, to recruit osteoclasts, and to cause inflammatory osteolysis. Moreover, by entering eukaryotic cells, staphylococci hide from the host immune defenses and shelter from the extracellular antibiotics. Thus, infection persists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…In order to shed more light on the different behavior observed in these strains, we also determined their influence on the gene expression of IL-6, TNF-α, TGF-β1, and GAPDH as well as Nrf2 and its downstream effector heme oxygenase 1 (HO-1). The human MG-63 osteoblast-like cell line was selected not only because it represents a validated model to study the pro-inflammatory response to bacterial infection [27][28][29], but also because shows a number of features typical of an undifferentiated osteoblast phenotype including the synthesis of collagen types I and III, a low basal expression of alkaline phosphatase which is increased following 1,25-dihydroxyvitamin D (1,25(OH)2D) administration, and the production of osteocalcin in the presence of 1,25(OH)2D [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In order to shed more light on the different behavior observed in these strains, we also determined their influence on the gene expression of IL-6, TNF-α, TGF-β1, and GAPDH as well as Nrf2 and its downstream effector heme oxygenase 1 (HO-1). The human MG-63 osteoblast-like cell line was selected not only because it represents a validated model to study the pro-inflammatory response to bacterial infection [27][28][29], but also because shows a number of features typical of an undifferentiated osteoblast phenotype including the synthesis of collagen types I and III, a low basal expression of alkaline phosphatase which is increased following 1,25-dihydroxyvitamin D (1,25(OH)2D) administration, and the production of osteocalcin in the presence of 1,25(OH)2D [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Serratiopeptidase is a natural molecule that is being used for decades, hence commonly considered as safe. The safety of this enzyme in different areas of therapeutics is supported by several studies [ 15 , 19 , 22 , 48 , 54 , 72 ] in which no side effects or adverse events were reported. However, some studies have reported adverse effects of this molecule, but at a rare frequency.…”
Section: Absorption and Safety Of Serratiopeptidasementioning
confidence: 80%
“…Further, authors suggested the need for research to identify the mechanism of action of serratiopeptidase in biofilm regulation that is unrelated to proteolytic activity. Recently, [ 54 ] evaluated the anti-biofilm ability of serratiopeptidase against Staphalococcus aureus infection on osteoblastic MG-63 cells. The pro-inflammatory chemokine MCP-1 was used as an immunological marker.…”
Section: Application Of Serratiopeptidase In Therapeuticsmentioning
confidence: 99%
“…the level of SA internalization is ca. 17% in human embryonic kidney cells (12), 8% in endothelial cells (12), 2% in human alveolar epithelial cells (A549) (K. Moreau, unpublished data), <1% HELA epithelial cells (13), <1% within osteoblast (14) and <2% in osteoclast (15). We could demonstrate that this high rate of internalization depends on several of the known pathways of S. aureus internalization with a preeminence of the FnBP-Fibronectin-α5β1 integrin-mediated pathway.…”
Section: Discussionmentioning
confidence: 99%